Corporal and Discourse Fuzzy Boundaries. The Partaking of Experience in Simone de Beauvoir’s Monologue - Marginean, Alexandra Roxana (European Scientific Journal, ESJ, 2018)
The paper sets out to analyze the multiple mirroring taking place between various aspects of the narrative reality in Simone de Beauvoir’s Monologue and suggested in terms of broken imagery. We seek to prove the unity and harmony existing in this disheveled text, which one may find difficult to make sense of upon a first reading. The aim is to reveal the way in which, in fact, the smallest details symphonically converge towards the main idea(s), in a finely-tuned and thought-over masterwork that the short story at hand obscures itself from being upon a superficial glance. Starting from corporal references, which abound in the text, we analyze the way in which these intertwine with and reflect the main themes – femininity and feminism, aggression and trauma, sexuality, motherhood, the obsession of contrasts, material and metaphorical obstructions and flows, patriarchy and truthfulness – and are reunited towards a bitter (and, as the protagonist claims, a more honest) interpretation of reality. The approach also proposes the acceptance of paradox, present in the notion of unity in difference, of fuzzy concepts, pointing to deconstructive construction and to the creation of broken identity. The demonstration ultimately resorts, for explanatory reasons, to the image of the partaking, as a metaphor for the process of using bits and pieces to the purpose of attaining communion, pieces which both aren’t and at the same time are the Whole.